Multi-partnership: the way forward for Agrodok - Agromisa; Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
Discussions focused on content generation, editorial input, handbook design and the use of web2.0 tools to facilitate collaboration between authors and resource persons...